2016
DOI: 10.1038/ng.3725
|View full text |Cite|
|
Sign up to set email alerts
|

Contribution of copy number variants to schizophrenia from a genome-wide study of 41,321 subjects

Abstract: Copy number variants (CNVs) have been strongly implicated in the genetic etiology of schizophrenia (SCZ). However, genome-wide investigation of the contribution of CNV to risk has been hampered by limited sample sizes. We sought to address this obstacle by applying a centralized analysis pipeline to a SCZ cohort of 21,094 cases and 20,227 controls. A global enrichment of CNV burden was observed in cases (OR=1.11, P=5.7×10−15), which persisted after excluding loci implicated in previous studies (OR=1.07, P=1.7 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

31
906
8
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 928 publications
(948 citation statements)
references
References 35 publications
31
906
8
3
Order By: Relevance
“…There is a similar 10-fold enrichment of deletions and duplications in ASD cohorts (11,12), and both CNVs have large effects on IQ (Z scores of 1.5 and 0.8, respectively) and Social Responsiveness Scale (SRS) (Z scores of 1 and 2, respectively) (10,(13)(14)(15). However, there are phenotypic differences between both CNVs: the 10-fold enrichment in schizophrenia cohorts (16,17) is only observed for duplications, and only deletions affect measures of language by 1.5 Z scores (18). Previous studies demonstrated "mirror" effects of both CNVs on head circumference and body mass index (13,19).…”
mentioning
confidence: 94%
“…There is a similar 10-fold enrichment of deletions and duplications in ASD cohorts (11,12), and both CNVs have large effects on IQ (Z scores of 1.5 and 0.8, respectively) and Social Responsiveness Scale (SRS) (Z scores of 1 and 2, respectively) (10,(13)(14)(15). However, there are phenotypic differences between both CNVs: the 10-fold enrichment in schizophrenia cohorts (16,17) is only observed for duplications, and only deletions affect measures of language by 1.5 Z scores (18). Previous studies demonstrated "mirror" effects of both CNVs on head circumference and body mass index (13,19).…”
mentioning
confidence: 94%
“…As a result, many additional CNVs have now been reported to be associated with schizophrenia. These are described in detail below and summarized in Table 1, which includes those that reach significance in the largest case/control CNV analysis to date, on 41,321 cases and controls [31] and have been previously reported.…”
Section: High-penetrance Genetic Variationmentioning
confidence: 99%
“…It contains the CHRNA7 gene encoding the A7 nicotinic acetylcholine receptor, previously linked to many psychiatric phenotypes including schizophrenia [51]. The 1q21.1 CNV was first reported by the International Schizophrenia Consortium to increase the risk when deleted [52] and later the reciprocal duplication was also found in excess [31, 53] in schizophrenia patients. Like the 16p11.2 CNV, reciprocal phenotypes have been described for the 1q21.1 CNV.…”
Section: High-penetrance Genetic Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Stephan Ripke is an expert in statistical genetics at Harvard Medical School and Charité Universitaetsmedizin Berlin. His work and methodological input were vital for the recent progress in the characterization of genetic signatures of frequent psychiatric disorders including polygenetic effects and copy number variation [34-38], which might also be informative for a better understanding of the inherited liability for neurodegenerative disease. Neuroimaging has proven valid both for the early diagnosis of neurodegenerative disorders [1, 2], the noninvasive assessment of molecular and metabolic properties [39, 40], and also as a measure of therapeutic target engagement [9].…”
mentioning
confidence: 99%